Recent Progress in Homogeneous Catalytic Dehydrogenation of Formic Acid - Naoya Onishi; Ryoichi Kanega; Hajime Kawanami; Yuichiro Himeda (Molecules, 2022)
Recently, there has been a strong demand for technologies that use hydrogen as an energy carrier, instead of fossil fuels. Hence, new and effective hydrogen storage technologies are attracting increasing attention. Formic acid (FA) is considered an effective liquid chemical for hydrogen storage because it is easier to handle than solid or gaseous materials. This review presents recent advances in research into the development of homogeneous catalysts, primarily focusing on hydrogen generation by FA dehydrogenation. Notably, this review will aid in the development of useful catalysts, thereby accelerating the transition to a hydrogen-based society.